Comorbid attention deficit hyperactivity disorder and substance use disorder complexity and chronicity in treatment‐seeking adults. (18th March 2015) - Young, Jesse Tyler; Carruthers, Susan; Kaye, Sharlene; Allsop, Steve; Gilsenan, Joanne; Degenhardt, Louisa; van de Glind, Geurt; van den Brink, Wim; Preen, David
Abstract Introduction and Aims Attention deficit hyperactivity disorder (ADHD) is a known risk factor for substance use disorder (SUD); however, the potential additive contribution of comorbid ADHD to drug‐specific dependence in SUD populations is largely unknown. The current study aimed to assess this association between ADHD symptoms and drug‐specific SUD complexity and chronicity. Design and Methods A cross‐sectional survey was administered to a convenience sample of 489 adults receiving SUD treatment at 16 Australian drug and alcohol treatment centres between September 2010 and August 2011. Participants were screened for adult ADHD symptoms using the Adult ADHD Self‐Report Scale. Associations between ADHD screening status and drug‐specific SUD complexity and chronicity were assessed using multivariate logistic and modified Poisson regression analysis, controlling for a range of potential confounders. Results Overall, 215 (44%) patients screened positive for concurrent adult ADHD and SUD. After Simes' correction, a significant positive association was observed between ADHD screening status and current amphetamine SUD (odds ratio (OR) = 1.85; 95% confidence interval (CI): 1.19–2.36). Patients who screened positive for ADHD were significantly more likely to report SUD history for heavy alcohol use (OR = 2.05; 95% CI: 1.21–3.45) and amphetamine (OR = 1.96; 95% CI: 1.26–3.06) as well as significantly increased risk of moderate (3–4 years) duration for benzodiazepine and amphetamine SUDs and long (≥5 years) duration for alcohol, opiates other than heroin or methadone, and amphetamine SUDs. Discussion and Conclusions The findings provide evidence that there is increased drug dependence complexity and chronicity in treatment‐seeking SUD patients who screen positively for ADHD, specifically for amphetamine, alcohol, opiates other than heroin or methadone, and benzodiazepines. [Young JT, Carruthers S, Kaye S, Allsop S, Gilsenan J, Degenhardt L, van de Glind G, van den Brink W, Preen D. Comorbid attention deficit hyperactivity disorder and substance use disorder complexity and chronicity in treatment‐seeking adults. Drug Alcohol Rev 2015;34:683–93]